ANALISIS KEMITRAAN DALAM MEWUJUDKAN SUSTAINABLE DEVELOPMENT GOALS (SDGS) DI DESA BIRINGALA KECAMATAN BAROMBONG KABUPATEN GOWA - Ramadhani, Citra; Madani, Muhlis (Universitas Muhammadiyah Makassar, 2022)
This study purposed to find out institutional partnerships in realizing the Sustainable Development Goals (SDGs) in Biringala Village, Barombong District, Gowa Regency. The research method used qualitative research. It purposed to understand the abilities of the research subjects, while the data collection techniques used the methods of observation, interviews and document studies. the number of informants as many as 9 people. Data analysis techniques used data collection, data reduction, data presentation and conclusions. Then, the data validation technique used source, technique and theoretical triangulation. The results showed that the Partnership Analysis in Realizing Sustainable Development Goals (SDGs) in Biringala Village, Barombong District, Gowa Regency was running well but not yet effective based on the indicators of partnership success according to the Directorate General of P2L PM in Kuswidanti, namely, Input Indicators, Process Indicators, Output Indicators, and Indicators Outcome. Input indicators in partnership management were still not effective, planning process indicators in management there were constraints on village fund budgets were still minimal, organizational output indicators need to improve tourism village management and partnership management outcome indicators to improve Tourism Villages.